Partners for progress : education and the private sector in Latin America and the Caribbean - Puryear, Jeffrey M. (Americas Society New YorkUS, 1997)
Presents case studies that demonstrate business involvement in education. Identifies and describes the diverse approaches to business-education partnerships.